The position of Reading as a transversal skill in the study programs for primary school teachers in Costa Rica. (Innovaciones Educativas, 2020)
This article results from the research developed by the Costa Rican branch of The Central American and Caribbean Early Literacy Network (RedLEI) and in particular, this paper seeks to define whether the didactic sequence of the study programs for teachers in training approach reading as a transversal skill or if their approach is merely instrumental as a teaching subject and in isolated curricular blocks. To do this, a mapping of the current Primary Education undergraduate programs. Also, analyses and categorization of their courses were made in four dimensions: Spanish (general), Literacy, Didactics of Children’s language, and literature. Aspects considered as quantitative characterization of how the programs approach the skill at the undergraduate stage were: number of courses offered, credits, and didactic sequence according to their position in the curriculum. The obtained results for the 19 study programs that were analyzed led to the conclusion that the majority (n=11) of them focus their attention in the courses regarding the didactics when it comes to literacy, language, or both; without training or promoting reading habits and general language skills in prospect teachers through specific training actions in reading culture at a curriculum level. That certainly undermines the country’s aspiration to train a new generation of teachers who are avid readers themselves.
Keywords: Reading; teachers; Costa Rica; primary school teacher training; teacher training; university